ADOLESCENT STUDENTS’ EXPERIENCE AND PERCEIVED PARENTAL SUPPORT IN INFORMAL DIGITAL ENGLISH LEARNING - Azwar, Taufik Akbar; Yunita, Wisma (ELTR Journal, 2025)
The study has contributed to filling the gap in the literature by exploring the perceived parental support in informal digital English learning. Few earlier studies have addressed the parental support issue within informal digital English learning contexts. This study thus aimed to find out students’ lived experiences and their perceived parental support towards their informal digital English learning activities. To this end, a narrative inquiry study design was employed. Two adolescent students who had been engaging in informal digital English learning from an early age were recruited for this study. The findings of this study reveal that the students perceived informal digital English learning as a great tool to self-develop their English language. In addition, learning enjoyment contributed to their digital English learning practices. Four types of parental support were identified. Information, material, autonomy, and emotional support from their parents shape their informal digital English learning activities. This study thus suggests that there needs to be a collaboration between parents and teachers to promote informal digital English learning.  Proper policies and guidelines are still required to help parents effectively support their children in informal digital English learning activities.